Globalisation, inequality and redistribution - Kjetil Bjorvatn; Bertil Tungodden (University of Oslo, Department of Economics, 2004)
The present paper seeks to explain the pattern of income redistribution in a globalised world of increased market income inequality and lower costs of factor mobility. In some countries, larger market income inequality has been met by an increased redistributive effort, thus keeping the distribution of disposable incomes relatively stable. In other countries, larger market inequality has been accompanied by a reduction in transfers, thus leading to growth in disposable income inequality. In our model, the initial level of market income inequality is crucial in explaining how an increase in this variable affects redistribution.
Keywords: F21; 330; Globalisation; Inequality; Redistribution; Majority voting; Globalisierung; Einkommensverteilung; Einkommensumverteilung; Public Choice; Theorie